Description of two new species in the genera Epectinaspis Blanchard and Strigoderma Burmeister (Coleoptera: Scarabaeidae: Rutelinae: Anomalini) - Ramírez-Ponce, Andrés; Curoe, Daniel (Zootaxa, 2014)
Two new species of the genera Epectinaspis Blanchard and Strigoderma Burmeister from Central America, E. costaricensis new species and S. ngabe new species, are described and illustrated. For each species and their closest congeners, their diagnostic characters are discussed and the taxonomic keys for their determination are modified.